Exit strategies of family businesses in Hungary - Mosolygó-Kiss, Ágnes; Kucséber, László; Szennay, Áron (Competitio, 2022)
The study aims to examine the ownership transmission strategies in the context of family firm succession in Hungary. The successful transfer of ownership, management and acquired experience at a family firm represents one of its greatest challenges; however, there is still a lack of understanding of the unique future strategies and succession outcomes of Hungarian family businesses. As a significant proportion of the founders of those family businesses established after the regime change (post-1989) are now reaching retirement age, a study of how such business organisations plan to survive the generational transition is highly relevant. This study applies a mixed methodology of quantitative and a qualitative analysis (e.g., in the case of IPOs). The results show that the average age of the examined family firm CEOs is higher than the global average and the majority of them plans to keep ownership and management within the family. Other exit strategies (i.e. initial public offerings, mergers and acquisitions) are not typical of the examined sample.